Effectiveness of the 3CM Learning Model Assisted by Differentiated Learning Modules to Improve Learning Achievement and Critical Thinking Skills - Dwi Susilo; Daru Wahyuni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
A teacher’s success in teaching can be observed through student learning outcomes. One of supporting factors for successful teaching is the used of learning model. This research aims to determine the effectiveness of Cool-Critical-Creative-Meaningfull (3CM) Learning Model Assisted by Differentiated Learning-Based Learning Modules to improve the academic achievement and the critical thinking skills of students at SMA Negeri 8 Malinau. This study employed a quantitative approach, with a quasi-experimental research method using a pretest and a posttest designs. The population consisted of 12th - grade students of SMA Negeri 8 Malinau, with 60 students sample divided into 2 classes, experimental class and control class, depended using a non-probability sampling technique. The experimental class is a class that is treated in the form of 3CM learning model assisted by differentiated learning-based learning modules, while the control class received a conventional treatment. Data collection for measuring learning outcomes and critical thinking skills was carried out through validated and reliable tests. Data analysis techniques used a homogeneity test with the F test and a hypothesis test with an Independent Sample T test. The results showed that: 1) the average of student learning outcomes in the experimental class was 75,50, higher than the students in the control class, which was 65,50; and 2) the average of critical thinking skills test outcomes in the experimental class was 81,22, higher than that of the control class, which was 61,47. From these results, it was concluded that the 3CM learning model assisted by differentiated learning-based learning modules was effective in improving student’s learning outcomes and critical thinking skills.